A alteração de registro civil das pessoas transexuais: fundamentos jurídicos e cenário na jurisprudência brasileira - Celestino, Aline do Couto (2017)
The struggle for recognition and defense of the LGBTTI (Lesbian, Gay, Bisexual, Transvestite, Transsexual, Intersex) community rights is intimately connected to the fulfillment of the Federative Republic of Brazil goals, especially the ones regarding the respect for human’s dignity and diversity as well as the promotion of equality in its material dimension. Nevertheless, many further advances in this field remain to be made. As a clear example, there’s the recognition of the right to a name and to a legal sex suitable for the transsexual’s gender identity - which continues to lack adequate protection in the Brazilian legal system given the Parliament’s constant omission and due to the inexistence of a pattern related to the Public Administration’s regulation of the use of the social name. Given this scenario, the Judiciary is pressed to intervene to guarantee the fundamental rights of transsexual people. Despite the lack of harmony in judicial verdicts, there are both conventional and constitutional support that authorize the legal name and gender change for these people. Therefore, it seems necessary to review the existing infraconstitutional system - from the constitutional principles of human’s dignity, equality and non-discrimination viewpoint - in order to understand the transsexual experience and accept it under the legal system. This understanding is based on a new perspective of the Law: one that no longer sees people only through their biopsychological references, but in a contextualized way, through social relations. Therefore, the propose of this research is to analyze not only the possible grounds for judicial decisions that recognize the right to legal name and gender change for transsexual people according to their gender identity, but also how Brazilian Courts have been giving their verdicts. Finally, this paper intends to reflect on Judiciary’s limits and legitimacy in consequence of other branches inertia, with the main purpose of mapping the most appropriate strategy to defend transsexual people rights